PERLINDUNGAN PRA PENEMPATAN CALON PEKERJA MIGRAN INDONESIA OLEH DINAS TENAGA KERJA DAN TRANSMIGRASI KOTA KUPANG MENURUT UNDANG-UNDANG NOMOR 18 TAHUN 2017 TENTANG PERLINDUNGAN PEKERJA MIGRAN INDONESIA - Dethan, Oskar Nomphi Michael; Pello, Helsina Fransiska; Nubatonis, Orpa Juliana (Petitum Law Journal, 2025)
This research focuses on the legal protection of Indonesian Migrant Workers (PMI) in the pre-deployment phase, as implemented by the Department of Manpower and Transmigration of Kupang City in accordance with Law Number 18 of 2017 on the Protection of Indonesian Migrant Workers. The study aims to comprehensively understand the legal protection applied during the pre-deployment phase and identify the obstacles faced in its implementation. Using an empirical legal approach and direct interviews with Department staff and prospective PMI registered in the SIAPKERJA application, the research explores the administrative and technical processes conducted by the Department. The findings reveal that the Department strives to provide comprehensive protection through document validation, training, and interagency coordination. However, challenges such as limited training facilities, insufficient socialization at the village level, and the negative role of brokers still persist. Cooperation between local government and related institutions, such as BP3MI, is crucial to achieving optimal protection for prospective migrant workers. These findings offer recommendations for improving the protection mechanisms for migrant workers in the future.